Modified aluminum silicate wool board and preparation method thereof

By adding a strong crosslinking agent to the aluminum silicate cotton plate and compounding it with a silicon-based sol, the problem of insufficient mechanical properties of the existing aluminum silicate cotton plates is solved, and higher tensile, compressive and flexural strength is achieved. Ensures thermal stability.

CN119409478APending Publication Date: 2025-02-11天辰(天津)生物科技有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311469343.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-27
Filing Date
2023-11-07
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing aluminum silicate cotton plates are easily damaged due to external loads during construction and service, resulting in thermal insulation failure. Their mechanical properties are poor and cannot meet the requirements of various usage environments.

Method used

By combining the aluminum silicate cotton wool sheet with a silicon-based sol and adding a strong crosslinking agent to the aerogel, the bonding strength of the aluminum silicate fiber and the aerogel is improved, and the mechanical properties of the plate are enhanced.

Benefits of technology

The mechanical properties of the modified aluminum silicate cotton plate are significantly improved, including tensile, compressive and flexural strength, so that the plate can withstand higher loads and ensure thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004534567610000031
    Figure BDA0004534567610000031
  • Figure BDA0004534567610000041
    Figure BDA0004534567610000041
  • Figure BDA0004534567610000101
    Figure BDA0004534567610000101
Patent Text Reader

Abstract

The invention relates to a modified aluminum silicate wool board and a preparation method thereof, and belongs to the technical field of thermal insulation materials. The composite material is formed by compounding silicon dioxide aerogel and aluminum silicate wool, a strong cross-linking agent is added into the aerogel, the bonding strength of aluminum silicate fibers and the aerogel is improved, the strong cross-linking agent is modified by substitution reaction of trithiocyanuric acid and 11-chloro-1-undecene and introduction of a structure with a long chain and an end double bond, and the strength of the aluminum silicate fibers and the strength of the aerogel are improved. According to the present invention, aluminum silicate fibers are subjected to end double bond click reaction and grafted triethoxysilane structure modification to form the aerogel, the sulfur-nitrogen structure in the strong cross-linking agent forms chelating anchoring with the aluminum silicate fibers, and participates in the cross-linking condensation of the silicon-based sol, such that the bridging effect is provided, and the bonding strength of the aerogel and the aluminum silicate fibers is substantially improved; compared with an existing aluminum silicate fiber reinforced aerogel plate, the aluminum silicate fiber reinforced aerogel plate has more excellent mechanical property, can bear higher load in the construction and service process, and ensures heat insulation stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal insulation materials, and specifically relates to a modified aluminum silicate wool board and a preparation method thereof. Background Art

[0002] In the field of thermal insulation materials, silica aerogel has high porosity, low density and excellent thermal insulation performance due to its porous nanostructure. Its density can be as low as 0.003g / cm 3 The thermal conductivity at room temperature can reach 0.013W / (m·K), which is almost half of the thermal conductivity of air under the same conditions. It has great application potential in the aerospace field and civil fields such as aerogel energy-saving windows, aerogel coatings, and aerogel new panels. However, pure silica aerogel has the disadvantage of poor mechanical properties due to its high porosity and cannot meet the requirements of various use environments.

[0003] Aluminum silicate wool is made of raw materials such as alumina and silicate, which are melted at high temperature, and then blown or spun to generate fibers, which are then gathered into fiber bundles using a cotton collector or a settling device. It has excellent high temperature resistance, and the sheet material contains a large number of pores and has good thermal insulation performance. However, the internal pores of aluminum silicate wool are large, which cannot hinder heat convection, and the thermal insulation performance is far lower than that of aerogel. In addition, aluminum silicate wool has poor shape retention ability and generally needs to be packaged before use.

[0004] In the prior art, the technology of compounding aerogel and fiber materials using the sol-gel method is relatively mature. For example, Chinese patent application 202111365505.4 discloses combining silica aerogel with fiber to obtain a board with good mechanical properties. There are countless such public technologies. However, in these technical schemes, the fiber and the aerogel are combined by intermolecular forces or cohesive forces after cross-linking of the aerogel. The bonding strength between the two is not high, resulting in poor overall mechanical properties. When used in boards, they will inevitably be subject to external loads during construction and service, resulting in damage to the board and thus insulation failure. Summary of the invention

[0005] In order to solve the technical problems mentioned in the background technology, the purpose of the present invention is to provide a modified aluminum silicate wool board and a preparation method thereof.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A modified aluminum silicate wool board is prepared by compounding an aluminum silicate wool sheet and a silica-based sol, followed by aging and drying. The preparation method comprises the following steps:

[0008] Step S1: mix tetraethyl orthosilicate, a strong crosslinking agent and anhydrous ethanol, add deionized water and adjust the pH value of the mixture to 2-3 with dilute hydrochloric acid, heat to 40-50°C, apply mechanical stirring at 120-180 rpm, stir and hydrolyze at constant temperature for 1.2-1.5 hours, then add ammonia water to adjust the hydrolyzate to neutrality under high-speed stirring to obtain a silica-based sol;

[0009] Furthermore, the usage ratio of ethyl orthosilicate, strong cross-linking agent, anhydrous ethanol and deionized water is 0.1 mol: 15-25 mmol: 45-50 mL: 7-10 mL.

[0010] Step S2: Place the aluminum silicate cotton wool sheet in a vacuum impregnator, evacuate to below 100 Pa, inject silica-based sol to normal pressure, let it stand for 1 hour, remove the residual silica-based sol on the surface, place it in anhydrous ethanol for immersion and aging for 12 hours, take it out again and place it in n-hexane for replacement for 24 hours, then bake and dry it to constant weight to obtain a modified aluminum silicate wool board.

[0011] The strong cross-linking agent is prepared by the following method:

[0012] Step A1: preheat thiocyanate and tetrahydrofuran to dissolve, add a non-metallic salt acid-binding agent and mix, then control the temperature to 65-75°C, apply mechanical stirring at 240-480 rpm, add 11-chloro-1-undecene at a uniform speed, stir at a constant temperature for 2.5-3.5 hours, and remove tetrahydrofuran by rotary evaporation after the reaction. Wash the rotary evaporation substrate with water and dry it to obtain an intermediate.

[0013] Preferably, the non-metallic salt acid-binding agent is any one of triethylamine, pyridine and N-ethyldiisopropylamine.

[0014] Furthermore, the dosage ratio of thiocyanuric acid, 11-chloro-1-undecene, non-metallic salt acid-binding agent and tetrahydrofuran is 0.1 mol: 0.32-0.35 mol: 35-45 mL: 220-260 mL, 11-chloro-1-undecene is substituted with thiocyanuric acid to introduce a long-chain terminal double bond structure modification, and the specific reaction process can be expressed as follows:

[0015]

[0016] Step A2: Dissolve the intermediate and N,N-dimethylacetamide, add dimethylphenylphosphine and mix well, introduce nitrogen to replace the air, heat to 45-60°C, apply mechanical stirring at 180-240 rpm, and add 70-100 μW / cm 2 Under ultraviolet irradiation, 3-mercaptopropyltriethoxysilane was slowly added, and the total reaction time was controlled to be 4-5h to obtain a strong cross-linking agent.

[0017] Furthermore, the usage ratio of the intermediate, 3-mercaptopropyl triethoxysilane, dimethylphenylphosphine and N,N-dimethylacetamide is 0.1 mol: 0.31-0.32 mol: 50-80 mg: 150-200 mL, dimethylphenylphosphine is used as a catalyst, ultraviolet radiation is initiated, 3-mercaptopropyl triethoxysilane and the double bonds introduced in the intermediate click reaction, and the triethoxysilane structure is grafted into the intermediate molecular structure. The specific reaction process can be expressed as follows:

[0018]

[0019] Beneficial effects of the present invention:

[0020] The invention discloses a silicon dioxide aerogel composite aluminum silicate wool board. A strong crosslinking agent is added to the aerogel to improve the bonding strength between the aluminum silicate fiber and the aerogel, thereby improving the mechanical properties of the board. The strong crosslinking agent uses thiocyanate as a base material, and 11-chloro-1-undecene is used for substitution reaction to introduce a structural modification with a long chain and a double bond at the end into the thiocyanate molecule. Then, 3-mercaptopropyl triethoxysilane is click-reacted with the double bond at the end to graft the triethoxysilane structure modification. The sulfur-nitrogen structure in the strong crosslinking agent molecule can form a multi-site bond with the aluminum silicate fiber. Point strong chelation, and then after vacuum injection of silica-based sol, the strong cross-linking agent first chelates and anchors with the aluminum silicate fiber. With the cross-linking condensation of the silica-based sol, the strong cross-linking agent plays a bridging role, greatly improving the bonding strength between the aerogel and the aluminum silicate fiber. At the same time, the long-chain bridging structure plays a certain bonding toughness between the aerogel and the aluminum silicate fiber, making it difficult for the aluminum silicate fiber to peel off from the aerogel, giving full play to the strengthening effect of aluminum silicate. Compared with the existing aluminum silicate fiber reinforced aerogel sheet, it has more excellent mechanical properties, can withstand higher loads during construction and service, and ensure thermal insulation stability. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Example 1

[0023] This embodiment prepares a modified aluminum silicate wool board, and the specific implementation process is as follows:

[0024] 1) Preparation of strong crosslinking agent

[0025] 1.1. Preheat thiocyanate and tetrahydrofuran to 50°C and stir until dissolved, add triethylamine and mix evenly, then continue to heat to 75°C and keep constant temperature, apply mechanical stirring at 480rpm, add 11-chloro-1-undecene at a uniform speed, stir and react at constant temperature for 2.5h, remove tetrahydrofuran by rotary evaporation after the reaction, add 0.7 times the mass of water to the rotary evaporation substrate for washing, remove the aqueous phase, dry with hot air to constant weight, and obtain an intermediate. In the above reaction, the amount ratio of thiocyanate, 11-chloro-1-undecene, triethylamine and tetrahydrofuran is 0.1mol:0.35mol:45mL:260mL.

[0026] 1.2. Dissolve the intermediate and N,N-dimethylacetamide, add dimethylphenylphosphine and mix well, introduce nitrogen until a stable nitrogen flow is discharged to replace the air in the reactor, heat to 60°C, apply mechanical stirring at 240 rpm, and add 100 μW / cm 2 Under ultraviolet irradiation, 3-mercaptopropyltriethoxysilane is slowly added within 1.5 hours. After all the addition, the reaction is kept under constant temperature and irradiation with stirring. The total addition reaction time is controlled to be 4 hours to obtain a strong cross-linking agent. In the above reaction, the amount ratio of the intermediate, 3-mercaptopropyltriethoxysilane, dimethylphenylphosphine and N,N-dimethylacetamide is 0.1 mol: 0.32 mol: 80 mg: 200 mL.

[0027] 2) Preparation of plates

[0028] 2.1. Take tetraethyl orthosilicate, a strong crosslinking agent and anhydrous ethanol, mix them evenly, add deionized water to mix, and adjust the pH value of the mixture to 2 with hydrochloric acid at a concentration of 1 mol / L. Then, heat the mixture to 50°C, apply mechanical stirring at 180 rpm, and hydrolyze at constant temperature for 1.2 hours. Then, stir the hydrolyzate at 1000 rpm, and adjust the hydrolyzate to neutral with 0.5 mol / L ammonia water to obtain a silica-based sol. In the above reaction, the amount ratio of tetraethyl orthosilicate, a strong crosslinking agent, anhydrous ethanol and deionized water is 0.1 mol: 25 mmol: 50 mL: 10 mL. In the embodiment, the strong crosslinking agent is not purified after preparation. It is found in the experiment that a small amount of solvent N, N-dimethylacetamide can improve the dispersibility of the silica-based sol, which is conducive to its uniform filling into the aluminum silicate cotton wool sheet.

[0029] 2.2. Take aluminum silicate cotton wool sheets, the fiber diameter is about 3μm, and the density is about 120kg / m 3, thickness is 5mm. The same batch of raw materials are used in the embodiments. The aluminum silicate cotton wool sheet is placed in a vacuum impregnator, vacuumed to 100Pa, and silica-based sol is injected to normal pressure. The sheet is left to stand for 1 hour, and the sheet is taken out to scrape off the residual silica-based sol on the surface. The sheet is placed in anhydrous ethanol for immersion and aging for 12 hours. The aged sheet is then placed in n-hexane for replacement for 24 hours, and then placed in an oven to dry at 80°C for 3 hours, and then dried at 120°C for 5 hours to constant weight to obtain a modified aluminum silicate wool board.

[0030] Example 2

[0031] This embodiment prepares a modified aluminum silicate wool board, and the specific implementation process is as follows:

[0032] 1) Preparation of strong crosslinking agent

[0033] 1.1. Preheat thiocyanate and tetrahydrofuran to 50°C and stir until dissolved, add pyridine and mix evenly, then continue to heat to 65°C and keep constant temperature, apply mechanical stirring at 240rpm, add 11-chloro-1-undecene at a uniform speed, stir and react at constant temperature for 3.5h, remove tetrahydrofuran by rotary evaporation after the reaction, add 0.5 times the mass of water to the rotary evaporation substrate for washing, remove the aqueous phase, dry with hot air to constant weight, and obtain an intermediate. In the above reaction, the amount ratio of thiocyanate, 11-chloro-1-undecene, pyridine and tetrahydrofuran is 0.1mol:0.32mol:35mL:220mL.

[0034] 1.2. Dissolve the intermediate and N,N-dimethylacetamide, add dimethylphenylphosphine and mix well, introduce nitrogen until a stable nitrogen flow is discharged to replace the air in the reactor, heat to 45°C, apply mechanical stirring at 180 rpm, and add 70 μW / cm 2 Under ultraviolet irradiation, 3-mercaptopropyltriethoxysilane is slowly added within 2 hours. After all the addition, the reaction is kept under constant temperature and irradiation with stirring. The total addition reaction time is controlled to be 5 hours to obtain a strong cross-linking agent. In the above reaction, the amount ratio of the intermediate, 3-mercaptopropyltriethoxysilane, dimethylphenylphosphine and N,N-dimethylacetamide is 0.1 mol: 0.31 mol: 50 mg: 150 mL.

[0035] 2) Preparation of plates

[0036] 2.1. Take tetraethyl orthosilicate, a strong crosslinking agent and anhydrous ethanol and mix them evenly, add deionized water to mix, and adjust the pH value of the mixture to 3 with 1 mol / L hydrochloric acid, then heat the mixture to 40°C, apply mechanical stirring at 120 rpm, and hydrolyze at constant temperature for 1.5 hours. Then, stir the hydrolyzate at 800 rpm, and adjust the hydrolyzate to neutral with 0.5 mol / L ammonia water to obtain a silica-based sol. In the above reaction, the amount ratio of tetraethyl orthosilicate, a strong crosslinking agent, anhydrous ethanol and deionized water is 0.1 mol: 15 mmol: 45 mL: 7 mL.

[0037] 2.2. Place the aluminum silicate cotton wool sheet in a vacuum impregnator, evacuate to 100Pa, inject silica-based sol to normal pressure, let it stand for 1 hour, take out the sheet and scrape off the residual silica-based sol on the surface, soak it in anhydrous ethanol for 12 hours, then take the aged sheet and place it in n-hexane for replacement for 24 hours, then place it in an oven to dry at 80°C for 3 hours, and then dry it at 120°C for 5 hours to constant weight to obtain a modified aluminum silicate wool board.

[0038] Example 3

[0039] This embodiment prepares a modified aluminum silicate wool board, and the specific implementation process is as follows:

[0040] 1) Preparation of strong crosslinking agent

[0041] 1.1. Preheat thiocyanate and tetrahydrofuran to 50°C and stir until dissolved, add N-ethyldiisopropylamine and mix evenly, then continue to heat to 72°C and keep constant temperature, apply mechanical stirring at 360rpm, uniformly add 11-chloro-1-undecene, stir and react at constant temperature for 3h, after the reaction is completed, remove tetrahydrofuran by rotary evaporation, add 0.6 times the mass of water to the rotary evaporation substrate for washing, remove the aqueous phase, dry with hot air to constant weight, and obtain an intermediate. In the above reaction, the amount ratio of thiocyanate, 11-chloro-1-undecene, N-ethyldiisopropylamine and tetrahydrofuran is 0.1mol:0.33mol:40mL:240mL.

[0042] 1.2. Dissolve the intermediate and N,N-dimethylacetamide, add dimethylphenylphosphine and mix well, introduce nitrogen until a stable nitrogen flow is discharged to replace the air in the reactor, heat to 55°C, apply mechanical stirring at 240 rpm, and add 90 μW / cm 2 Under ultraviolet irradiation, 3-mercaptopropyltriethoxysilane is slowly added within 2 hours. After all the addition, the reaction is kept under constant temperature and irradiation with stirring. The total addition reaction time is controlled to be 4.5 hours to obtain a strong cross-linking agent. In the above reaction, the amount ratio of the intermediate, 3-mercaptopropyltriethoxysilane, dimethylphenylphosphine and N,N-dimethylacetamide is 0.1 mol: 0.31 mol: 70 mg: 180 mL.

[0043] 2) Preparation of plates

[0044] 2.1. Take tetraethyl orthosilicate, a strong crosslinking agent and anhydrous ethanol and mix them evenly, add deionized water to mix, and adjust the pH value of the mixture to 3 with 1 mol / L hydrochloric acid. Then heat the mixture to 45°C, apply mechanical stirring at 180 rpm, and hydrolyze at constant temperature for 1.3 hours. Then, stir the hydrolyzate at 1000 rpm, and adjust the hydrolyzate to neutral with 0.5 mol / L ammonia water to obtain a silica-based sol. In the above reaction, the amount ratio of tetraethyl orthosilicate, a strong crosslinking agent, anhydrous ethanol and deionized water is 0.1 mol: 20 mmol: 48 mL: 9 mL.

[0045] 2.2. Place the aluminum silicate cotton wool sheet in a vacuum impregnator, evacuate to 100Pa, inject silica-based sol to normal pressure, let it stand for 1 hour, take out the sheet and scrape off the residual silica-based sol on the surface, soak it in anhydrous ethanol for 12 hours, then take the aged sheet and place it in n-hexane for replacement for 24 hours, then place it in an oven to dry at 80°C for 3 hours, and then dry it at 120°C for 5 hours to constant weight to obtain a modified aluminum silicate wool board.

[0046] Example 4

[0047] This embodiment prepares a modified aluminum silicate wool board, and the specific implementation process is as follows:

[0048] 1) Preparation of strong crosslinking agent

[0049] 1.1. Preheat thiocyanate and tetrahydrofuran to 50°C and stir until dissolved, add N-ethyldiisopropylamine and mix evenly, then continue to heat to 68°C and keep constant temperature, apply mechanical stirring at 360rpm, uniformly add 11-chloro-1-undecene, stir and react at constant temperature for 3.2h, after the reaction is completed, remove tetrahydrofuran by rotary evaporation, add 0.6 times the mass of water to the rotary evaporation substrate for washing, remove the aqueous phase, dry with hot air to constant weight, and obtain an intermediate. In the above reaction, the amount ratio of thiocyanate, 11-chloro-1-undecene, N-ethyldiisopropylamine and tetrahydrofuran is 0.1mol:0.34mol:40mL:250mL.

[0050] 1.2. Dissolve the intermediate and N,N-dimethylacetamide, add dimethylphenylphosphine and mix well, introduce nitrogen until a stable nitrogen flow is discharged to replace the air in the reactor, heat to 52°C, apply mechanical stirring at 240 rpm, and add 80 μW / cm 2Under ultraviolet irradiation, 3-mercaptopropyltriethoxysilane is slowly added within 1.8 hours. After all the addition, the reaction is kept under constant temperature and irradiation with stirring. The total addition reaction time is controlled to be 4.5 hours to obtain a strong cross-linking agent. In the above reaction, the amount ratio of the intermediate, 3-mercaptopropyltriethoxysilane, dimethylphenylphosphine and N,N-dimethylacetamide is 0.1 mol: 0.32 mol: 60 mg: 160 mL.

[0051] 2) Preparation of plates

[0052] 2.1. Take tetraethyl orthosilicate, a strong crosslinking agent and anhydrous ethanol and mix them evenly, add deionized water to mix, and adjust the pH value of the mixture to 2 with 1 mol / L hydrochloric acid. Then heat the mixture to 42°C, apply mechanical stirring at 180 rpm, and stir and hydrolyze at constant temperature for 1.5 hours. Then stir the hydrolyzate at 1000 rpm, and adjust the hydrolyzate to neutral with 0.5 mol / L ammonia water to obtain a silica-based sol. In the above reaction, the amount ratio of tetraethyl orthosilicate, a strong crosslinking agent, anhydrous ethanol and deionized water is 0.1 mol: 18 mmol: 50 mL: 8 mL.

[0053] 2.2. Place the aluminum silicate cotton wool sheet in a vacuum impregnator, evacuate to 100Pa, inject silica-based sol to normal pressure, let it stand for 1 hour, take out the sheet and scrape off the residual silica-based sol on the surface, soak it in anhydrous ethanol for 12 hours, then take the aged sheet and place it in n-hexane for replacement for 24 hours, then place it in an oven to dry at 80°C for 3 hours, and then dry it at 120°C for 5 hours to constant weight to obtain a modified aluminum silicate wool board.

[0054] Comparative Example

[0055] The preparation process of this comparative example is the same as that of Example 4, except that no strong crosslinking agent is added to the silica-based sol. The usage ratio of ethyl orthosilicate, anhydrous ethanol and deionized water is 0.1 mol: 35 mL: 4 mL, and the rest are exactly the same.

[0056] Take the plates prepared in Examples 1 to 4 and the comparative example, and use a QTM-500 thermal conductivity tester to detect the room temperature thermal conductivity of the plates; use a CMT6104 electronic universal testing machine to detect the tensile strength, compressive strength and flexural strength of the plates, where the compressive strength is expressed by the pressure value when the material strain is 50%, the initial preload is 5N, the pressure loading speed is 5N / s, and the flexural strength is measured by a three-point bending method with a span of 20mm; the specific test results are shown in Table 1:

[0057] Table 1

[0058]

[0059] It can be seen from the data in Table 1 that the thermal conductivity of the plate prepared by the present invention is similar to that of the existing aluminum silicate wool composite aerogel plate, both of which are lower than 0.03W / (m·k), showing good insulation ability. Among them, the tensile, compressive and flexural strengths of the plate prepared by the present invention are significantly better than those of the comparative example, showing excellent mechanical properties, and the plate can bear a larger load during service.

[0060] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0061] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a modified aluminum silicate wool board, characterized in that: The steps include: Step S1: mix tetraethyl orthosilicate, a strong crosslinking agent and anhydrous ethanol, add deionized water and adjust the pH value of the mixture to 2-3 with dilute hydrochloric acid, heat to 40-50°C, apply mechanical stirring at 120-180 rpm, stir and hydrolyze at constant temperature for 1.2-1.5 hours, then add ammonia water to adjust the hydrolyzate to neutrality under high-speed stirring to obtain a silica-based sol; Step S2: Place the aluminum silicate cotton wool sheet in a vacuum impregnator, evacuate to below 100 Pa, inject silica-based sol to normal pressure, let it stand for 1 hour, remove the residual silica-based sol on the surface, place it in anhydrous ethanol for immersion and aging for 12 hours, take it out again and place it in n-hexane for replacement for 24 hours, then bake and dry it to constant weight to obtain a modified aluminum silicate wool board.

2. The method for preparing a modified aluminum silicate wool board according to claim 1, characterized in that: Strong crosslinkers are made by the following steps: Step A1: preheating thiocyanate and tetrahydrofuran to dissolve, adding a non-metallic salt acid-binding agent and mixing, then controlling the temperature to 65-75°C, applying mechanical stirring at 240-480 rpm, adding 11-chloro-1-undecene at a uniform speed, stirring at a constant temperature for 2.5-3.5 hours, and removing tetrahydrofuran by rotary evaporation after the reaction, washing and drying the rotary evaporation substrate with water to obtain an intermediate; Step A2: Dissolve the intermediate and N,N-dimethylacetamide, add dimethylphenylphosphine and mix well, introduce nitrogen to replace the air, heat to 45-60°C, apply mechanical stirring at 180-240 rpm, and add 70-100 μW / cm 2 Under ultraviolet irradiation, 3-mercaptopropyltriethoxysilane was slowly added, and the total reaction time was controlled to be 4-5h to obtain a strong cross-linking agent.

3. The method for preparing a modified aluminum silicate wool board according to claim 2, characterized in that: The non-metallic salt acid-binding agent is any one of triethylamine, pyridine and N-ethyldiisopropylamine.

4. The method for preparing a modified aluminum silicate wool board according to claim 3, characterized in that: The dosage ratio of thiocyanate, 11-chloro-1-undecene, non-metallic salt acid-binding agent and tetrahydrofuran is 0.1 mol: 0.32-0.35 mol: 35-45 mL: 220-260 mL.

5. The method for preparing a modified aluminum silicate wool board according to claim 4, characterized in that: The usage ratio of the intermediate, 3-mercaptopropyltriethoxysilane, dimethylphenylphosphine and N,N-dimethylacetamide is 0.1 mol: 0.31-0.32 mol: 50-80 mg: 150-200 mL.

6. The method for preparing a modified aluminum silicate wool board according to claim 5, characterized in that: The usage ratio of ethyl orthosilicate, strong cross-linking agent, anhydrous ethanol and deionized water is 0.1 mol: 15-25 mmol: 45-50 mL: 7-10 mL.

7. A modified aluminum silicate wool board, characterized in that: The method is prepared by any one of claims 1 to 6.

Citation Information

Patent Citations

  • A SiO2 aerogel insulation board and its preparation method

    CN113998984B